Dialektika Agama Dan Budaya: Pendidikan Keluarga Dalam Bingkai Tradisi Sorogan Pada Pernikahan Masyarakat Karawang - Bustomi, Ahmad (Ri'ayah: Jurnal Sosial dan Keagamaan, 2024)
The current of westernization has spread widely in Indonesia, especially since the arrival of colonizers to the archipelago. People are more proud to use all forms originating from abroad in every line of their lives than using indigenous traditions and cultures of the archipelago. One of the traditions in the community that began to erode was the Sorogan tradition at weddings in Karawang Regency. This tradition has not appeared in some research dissemination media and this is very worrying and vulnerable to being lost to the times. Studies on sorogan even mostly discuss the pesantren learning method which has nothing to do with the marriage tradition in Karawang community families. The purpose of this study is to analyze family education in the Sorogan Tradition Frame at Karawang Community Weddings and the dialectics that occur between religion and culture in the Sorogan tradition. This research is a type of field research with a qualitative approach. The data collection methods used were observation, interviews and documentation. The respondents were Penghulu, religious leaders, community leaders and community elders in Karawang Regency. Data analysis techniques using the Miles and Huberman model are Data reduction, Display data and Conclusion drawing/verification. The results showed that: First, this sorogan wedding tradition educates brides-to-be about Cultural Preservation, Silaturahim, Responsibility, Respect for Parents, Avoiding Hostility and Gotong Royong.